2015
DOI: 10.1186/s12978-015-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal rate of caesarean section at population level? A systematic review of ecologic studies

Abstract: In 1985, WHO stated that there was no justification for caesarean section (CS) rates higher than 10–15 % at population-level. While the CS rates worldwide have continued to increase in an unprecedented manner over the subsequent three decades, concern has been raised about the validity of the 1985 landmark statement. We conducted a systematic review to identify, critically appraise and synthesize the analyses of the ecologic association between CS rates and maternal, neonatal and infant outcomes. Four electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
400
2
24

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(432 citation statements)
references
References 23 publications
6
400
2
24
Order By: Relevance
“…Several ecological studies have analysed the association between the mode of delivery and maternal, neonatal, and infant mortality, and identified an inflection point below which there was a strong association between caesarean section rates and mortality outcomes 2, 4, 12, 13, 14, 15, 16, 17, 18. A systematic review of ecological studies concluded that this point ranged from 9 to 16%, and at caesarean section rates above this threshold, there was no longer an association between caesarean section rates and maternal or infant mortality 30. Among the eight studies found, only two previous ecological studies controlled for socio‐economic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several ecological studies have analysed the association between the mode of delivery and maternal, neonatal, and infant mortality, and identified an inflection point below which there was a strong association between caesarean section rates and mortality outcomes 2, 4, 12, 13, 14, 15, 16, 17, 18. A systematic review of ecological studies concluded that this point ranged from 9 to 16%, and at caesarean section rates above this threshold, there was no longer an association between caesarean section rates and maternal or infant mortality 30. Among the eight studies found, only two previous ecological studies controlled for socio‐economic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It reflects especially on the rate of vaginal birth after previous cesarean section where very few obstetricians can take decision for vaginal delivery. They have overviewed the main problems associated with increased rate of cesarean section [8][9][10]. It seems the main reason of repeat cesarean sections is the uterine scar dehiscence after previous cesarean section, which can produce rupture of the uterus through dehiscence scar during pregnancy [43] or delivery in about 70% of cases.…”
Section: Dr David Chuderland From Genesort Ltdmentioning
confidence: 99%
“…In the US, maternal mortality has increased from 10 (1998) to 14/ 100.000 (2004) due to placenta percreta, scars or emergency hysterectomy after a complication induced by a (previous) Cesarean [10]. Confidential inquiries about the specified complications as the direct or indirect cause of combined mortality or severe morbidity are rare.…”
mentioning
confidence: 99%
“…Since 1985, a C-section rate of 10-15 % has been deemed optimum by international health-care community [6]. When C-section rates rise towards 10% across a population, maternal and newborn deaths decrease; when they are higher than 15% , there is no evidence of reduced morbidity [6]. Even though, the C-section rates rise up 70% in some countries, the standard evidence-based quidelines are not established [3,2].…”
mentioning
confidence: 99%
“…Although the aim of caesarean section is the decreasing of newborn and mother and morbidity rates, the complications of the caesarean section can be result in disability or death of the baby and mother [3][4][5]. Since 1985, a C-section rate of 10-15 % has been deemed optimum by international health-care community [6]. When C-section rates rise towards 10% across a population, maternal and newborn deaths decrease; when they are higher than 15% , there is no evidence of reduced morbidity [6].…”
mentioning
confidence: 99%